(untitled) (LACCEI, 2024)
The objective of the present investigation is to determine the level of contamination of the karstic aquifers by infiltration of whey in the San Francisco, Florida and Vigaspampa hamlets, Celendín province. Cajamarca, Peru 2021. For which the mapping of the study area was carried out, to determine the calcareous formations, as well as the elevation and/or depressions that favor the emanation of the springs, to later be complemented by the sampling of 3 springs specifically located in each hamlet, thus, to later carry out the physicochemical, chemical and biological analyzes of the samples sent to the laboratory. Later, with the database, the Easy Quim 4.0 Software was used to appreciate the graphs that show the polluting variations of the analyzed waters, using the Piper and/or Schoeller Diagram. Then, a comparison of the three test points was made, in order to be able to recognize the contamination of the groundwater, since the results obtained from the laboratory were evaluated, with the environmental quality standards (ECA) established by the Peruvian government in the Supreme Decree No. 004-2017-MINAM which establishes the national standards for the environmental quality of category A1 water in the Peruvian territory, in addition to the maximum permissible limits (LMP) DS No. 031-2010-SA for effluents of domestic wastewater, from the housing sector. In this way, the results were found with a contamination much greater than that provided by Peruvian laws, in environmental quality, taking into account the geology of the study area.